PERKEMBANGAN MORAL KOHLBERG DAN PERKEMBANGAN MORAL ABDULLAH NASIKH ULWAN - Amaliya Mufarroha; Abdul Hakim (LPPM IAI Nazhatut Thullab, 2020)
This descriptive qualitative research study discusses moral development according to Kohlberg and Nasih Ulwan. Humans as physical and spiritual beings need knowledge and wisdom that hold morally as an effort to prevent liberal-secular efforts that want to destroy morals. Kolhberg expressed that the concept of morality is more a philosophical concept (ethical) than just a concept of behavior. The strength of the theory is that phasing can make it easier for people to predict one's moral development. However, Kohlberg's moral development still raises various kinds of criticism from experts. While Nasih Ulwan emphasized moral education or morals on matters of amar ma'ruf and nahi munkar since childhood, which originated from the Qur'an and the Prophet's example. Respecting and valuing humans as humans, and treating humans as humans, is the main goal of moral education. Parent's full attention is tazkiyah an-nafs. Both have advantages and disadvantages, but they still contribute greatly to Islamic education. Kata Kunci: Perkembangan Moral, Kohlberg, Akhlak Islam, Abdullah Nasikh Ulwan